IDENTIFIKASI MINAT BELAJAR SISWA BERDASARKAN KARAKTER INDIVIDU SISWA - Riska Riani (LPPM Universitas Cipta Mandiri, 2024)
The aim of the research is to identify students' learning interests based on the students' individual characteristics. This type of research is a study of literature from various scientific sources obtained, books, reports, journals, modules and other sources. The research was conducted in May-June 2024. Most people show a tendency towards one particular learning style. Based on the results; 29% visual, 34% auditory and 37% kinesthetic. Additional information states that when you reach adulthood, your learning style tends to be a visual style.